2019
DOI: 10.1021/acsomega.9b02412
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot SELEX: Identification of Specific Aptamers against Diverse Steroid Targets in One Selection

Abstract: Aptamers are well-established biorecognition molecules used in a wide variety of applications for the detection of their respective targets. However, individual SELEX processes typically performed for the identification of aptamers for each target can be quite time-consuming, labor-intensive, and costly. An alternative strategy is proposed herein for the simultaneous identification of different aptamers binding distinct but structurally similar targets in one single selection. This one-pot SELEX approach, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
(77 reference statements)
0
33
1
Order By: Relevance
“…The feature set of HTS-SELEX specialized software in the future can be expanded to realize the power of HTS experiments to a greater extent. For instance, the specific analysis of HTS-SELEX results aiming to investigate aptamer structure and the function relationship and aptamer specificity is performed with the hand data operation [ 52 , 76 , 78 , 79 , 81 ] or with the adaptation of non-specialized tools [ 80 ]. The accounting of negative and non-targeted selections required for aptamer specificity control as well as the analysis of the binding patterns of the sequences can be integrated in software tools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The feature set of HTS-SELEX specialized software in the future can be expanded to realize the power of HTS experiments to a greater extent. For instance, the specific analysis of HTS-SELEX results aiming to investigate aptamer structure and the function relationship and aptamer specificity is performed with the hand data operation [ 52 , 76 , 78 , 79 , 81 ] or with the adaptation of non-specialized tools [ 80 ]. The accounting of negative and non-targeted selections required for aptamer specificity control as well as the analysis of the binding patterns of the sequences can be integrated in software tools.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is based on the hypothesis that aptamer preferential abundance is related to the specificity. DNA aptamers to the steroids estradiol, progesterone, and testosterone were selected in one-pot SELEX and then identified based on HTS analysis of the pools obtained from the differential selection step [ 78 ]. The revealed aptamers displayed the desired specificity [ 78 ].…”
Section: Insights To Aptamer Selection Process Derived From Hts Damentioning
confidence: 99%
See 1 more Smart Citation
“…Va lenzano et al [127] also used enrichment to identify highly specific tyramine-binding aptamers from HTS data, in ap rocess that involved counter-selection against the structurally similar molecules histamine and tryptamine.T hey found that the most abundant sequence prior to the initiation of counterselection was completely removed after counter-selection, indicating it had poor specificity,w hereas sequences specific to the target were greatly enriched. Theb est aptamer they identified had as ub-micromolar K D ,w ith lower binding affinity for the counter-targets.H TS has also been used to monitor changes in the population of certain sequences during SELEX, which can be used as indicator of the specificity of as equence,o rc ombined with counter-SELEX to isolate aptamers with specific binding profiles.J auset-Rubio et al [119] used HTS to identify aptamers that are highly specific or cross-reactive to the steroid hormones estradiol, progesterone,a nd testosterone.T hey first pre-enriched al ibrary pool using estradiol, and then performed as ingle round of selection against the three individual compounds in parallel. They identified specific aptamers for each target and cross-reactive aptamers by sequencing the pre-enriched pool and the three parallel pools and then analyzing the change in frequency of each sequence in all pools.S equences enriched in all pools were found to be cross-reactive,w hile sequences enriched only in as ingle pool were specific.…”
Section: Monitoring Selex and Identification Of Aptamermentioning
confidence: 99%
“…Va lenzano et al [127] also used enrichment to identify highly specific tyramine-binding aptamers from HTS data, in ap rocess that involved counter-selection against the structurally similar molecules histamine and tryptamine.T hey found that the most abundant sequence prior to the initiation of counterselection was completely removed after counter-selection, indicating it had poor specificity,w hereas sequences specific Angewandte Chemie Aufsätze to the target were greatly enriched. Theb est aptamer they identified had as ub-micromolar K D ,w ith lower binding affinity for the counter-targets.H TS has also been used to monitor changes in the population of certain sequences during SELEX, which can be used as indicator of the specificity of as equence,o rc ombined with counter-SELEX to isolate aptamers with specific binding profiles.J auset-Rubio et al [119] used HTS to identify aptamers that are highly specific or cross-reactive to the steroid hormones estradiol, progesterone,a nd testosterone.T hey first pre-enriched al ibrary pool using estradiol, and then performed as ingle round of selection against the three individual compounds in parallel. They identified specific aptamers for each target and cross-reactive aptamers by sequencing the pre-enriched pool and the three parallel pools and then analyzing the change in frequency of each sequence in all pools.S equences enriched in all pools were found to be cross-reactive,w hile sequences enriched only in as ingle pool were specific.…”
Section: Monitoring Selex and Identification Of Aptamermentioning
confidence: 99%